Clinical characteristics of children with MIS-C fulfilling classification criteria for macrophage activation syndrome - Buda, Piotr; Strauss, Ewa; Januszkiewicz-Lewandowska, Danuta; Czerwinska, Ewa; Ludwikowska, Kamila; Szenborn, Leszek; Gowin, Ewelina; Okarska-Napierała, Magdalena; Kuchar, Ernest; Ksia̧zyk, Janusz (Frontiers in Pediatrics, 2022)
Background: Macrophage activation syndrome (MAS) is a potentially life-threatening complication of various inflammatory disorders, including multisystem inflammatory syndrome in children (MIS-C). MIS-C refractory to treatment should raise suspi¬cion of MAS, which can be fatal if a definitive diagnosis is delayed. Unfortunately, there is a lack of data on MAS in children with MIS-C. Objective: Our study aims to analyze the clinical course of macrophage activation syndrome in children, evaluate risk factors for the development, and to identify predictive factors for the treatment in pediatric intensive care unit of MAS-MIS-C children. Material and Methods: We analyzed data from the Polish MIS-C registry of the MultiOrgan Inflammatory Syndromes COVID-19 Related Study. Patients were treated according to national guidelines (Polish Pediatric Society) based on international consensus. Results: 274 children met the study inclusion criteria. Fifty-nine patients were diagnosed with MAS, and 9 patients required admission to the pediatric intensive care unit (PICU). MIS-C patients with MAS were significantly older than patients without MAS (median 11.2 vs. 8.1 years). Multivariable analysis showed that age, symptoms characteristic of atypical Kawasaki disease, and skin erosion were significant factors indicating the risk of MAS in MIS-C patients. Analysis of laboratory parameters showed that on admission, MIS-C patients with MAS had a significantly lower median of lymphocyte and platelet counts, albumin and sodium levels, and higher median levels of C-reactive protein, procalcitonin, ferritin, D-dimers, triglycerides, serum creatinine, urea, and gamma-glutamyl transpeptidase, and neutrophil count. Multivariate analysis showed that higher procalcitonin, ferritin, and fibrinogen levels at admission were predictive of MAS. Only elevated troponin level is a predictive factor of children with MAS requiring PICU hospitalization. No significant differences in treatment were found when comparing groups of children with MAS only versus those hospitalized in PICU. None of the patients required biological agents. Conclusions: The clinical course of MAS in MIS-C seems milder, treatment less aggressive, and the prognosis better than expected based on the current knowledge on MAS complicating other rheumatological diseases.